ANALISIS KETERAMPILAN DASAR MENGAJAR (MICRO TEACHING) MAHASISWA PROGRAM STUDI PENDIDIKAN GURU SEKOLAH DASAR STKIP AMAL BAKTI TA 2022-2023 - Tiolina Siregar, Hotma; Tarigan, Juniko Esra; Ginting, Adi Negara (JURNAL CURERE, 2023)
Micro (micro-teaching) is a form of training conducted to help pre-service teachers in mastering Basic Teaching Skills. Implementation of teaching which is then carried out in the learning process with colleagues (peer teaching) with the setting conditions and context of actual teaching and learning activities. Using specific skills and teaching with a small number of students (small group). Analysis of Basic Teaching Skills (Micro Teaching) for Elementary School Teacher Education Study Program STKIP AMAL BAKTI TA 2022-2023. The eight Basic Skills for Teaching Students in Subjects (Micro Teaching) in the overall implementation is good with a score percentage of 69.59%. The Basic Teaching Skills for PGSD students that stand out the most are the Skills of Giving Reinforcement (74.14%), while the skills that are the lowest are the Skills of Making Variations (64.86%).